Video Surveillance And Monitoring System For Examination Malpractice In Tertiary Institutions (International Journal of Engineering and Computer Science, 2017)
The objective of this paper is to design and develop a video surveillance and monitoring system that willprovide easy access to both live and archived images during and after an institutions examination. Mymotivation into this paper work is the rate at which students and staff of tertiary institutions participateand encourage examination malpractice. The paper methodology adopted for this paper work was byobservation. The top-down software design was adopted for this research. Prototype developmentmethodology was used in the development of the system and Microsoft visual studio 2010; using visualbasic in the .net framework was used as the programming language. The resultant outcome of this paperwas tested to make sure examination malpractice in tertiary institutions is brought to its lowest minimum,making sure all requirements are met and are working perfectly as expected, bringing all offenders anddefaulters involved in examination malpractice to book.